Features of the structural organization of mycelial actinobacteria communities in natural soils of Ukraine and Russia - Gryshko, V.M.; Syshchykova, O.V.; Zenova, G.M.; Chernov, I.Yu. (Reports of the National Academy of Sciences of Ukraine, 2014)
In the genetic horizons of chernozems, the share of actinomycetes in microbocenosis makes 30% of the total number of microorganisms. In the usual and southern chernozems, S. violaceomaculatus (section Roseus), S. sporoherbeus (section Azureus), S. aerionidulus (section Cinereus), S. enduracidicus (section Cinereus), and S. grisinus (section Cinereus) dominate. In the typical chernozem, actinomycetes from the genus Streptomyces, Micromonospora, Streptosporangium are also found. Representatives of the genus Streptosporangium in typical chernozems make a minor component. In the usual chernozem, the values of Berger–Parker index (or the specific variety of a community) is by 1.5 times more than in the southern chernozem. The high similarity of the communities of streptomycetes of these chernozem soils (Serensen’s coefficient is equal to 0.78) is found.